A branch and bound algorithm for optimal television commercial scheduling - Lu-Wen Liao (Mathematical Biosciences and Engineering, 2022)
In the current era of multimedia, television (TV) plays an important role in transmitting advertising messages. In addition, advertising is the primary source of revenue for the TV industry. Thus, a critical issue for TV stations is the scheduling of commercials in suitable advertising breaks on different TV channels to maximize revenue and minimize penalties. This type of TV commercial scheduling problem is similar to the machine scheduling problem, and both have availability constraints. However, the literature on TV commercial scheduling has not considered this perspective. Motivated by this, we consider the problem of scheduling commercials with specific service-level requirements on TV channels while minimizing the maximum lateness. The lateness of a commercial is defined to be its completion time minus its due date, and the maximum lateness is the maximum value of lateness among all commercials. We propose an exact branch and bound algorithm based on the LFJ (least flexible job first)/EDD (earliest due date first) rules and network flow methods, which were developed to solve the machine scheduling problem with availability constraints. Computational analysis shows that the bounding scheme proposed is highly effective, and a very low percentage of nodes is generated by the branch and bound algorithm. The algorithm can obtain an optimal solution for the problem.